Occupational and environmental exposures and lung cancer in an industrialised area in Italy. Issue 9 (18th August 2004) - Fano, V; Michelozzi, P; Ancona, C; Capon, A; Forastiere, F; Perucci, C A
Abstract : Aims: To investigate the effects of occupational exposures and residence near to industrial sites on lung cancer mortality in an area in Italy. Methods: 234 cases of lung cancer and 729 controls matched by sex, age, and date of death were enrolled. Environmental exposure was evaluated using historical residence data. A geographical information system was used to compute distances from residence to pollution source (cement factory, power plants, harbour) and an average distance was computed for each subject. Odds ratios (OR) and 95% confidence intervals (CI) in a logistic regression model were used to estimate the relative risk of lung cancer associated with the risk factors (smoking habits and occupational exposure) collected by questionnaire; ORs for distances from pollution sources and from city centre were computed, adjusting for smoking habits, education, and occupation. Results: Smoking habits (⩽10 cigarettes/day, OR = 2.28; 11–20, OR = 4.64; >20, OR = 6.61) and occupational exposure to asbestos (OR = 3.50) were significantly associated with lung cancer risk. Reported traffic level of area of residence and residence near the four sources were not associated with increased risk of lung cancer. There was a significantly increased risk for those residing outside the city centre, in the southern outskirts (OR = 1.51). Conclusions: The increased lung cancer risk observed in the area can partly be explained by occupational exposures. The increased risk in the outskirts of the city is consistent with the results of dispersion models that indicate high levels of pollutant deposition in the same area.